INCREASING STUDENT LITERACY THROUGH A CREATIVE APPROACH AT SDN 57 BANDA ACEH - Sri Hartati; Siti Mayang Sari (SENSEI RESEARCH CENTER, 2024)
Education is a critical aspect in shaping the future of young people, and literacy plays an important role in ensuring students' intellectual and social development. Increasing creative literacy is a key focus, incorporating art, innovation and creativity into learning to stimulate student interest and engagement. The aim of this research is to determine the increase in student literacy through a creative approach at SDN 57 Banda Aceh. This research uses a qualitative approach with descriptive research type. Based on the interview results, it shows that teachers play an important role as facilitators of creativity, using learning methods such as art projects and technology to design interesting learning experiences. Students responded positively, showed greater interest in literacy, and felt more motivated to read and write. However, challenges such as teacher readiness and resource availability still need to be addressed. Additional training is required to fully understand the integration of creativity in literacy learning, and time and resource constraints pose logistical obstacles. Involving parents is considered important, and SDN 57 Banda Aceh has involved parents through regular meetings and creative literacy activities.